Pengaruh Kombinasi Pupuk NPK dan Pupuk Hayati terhadap Populasi Total Mikroba Tanah dan Hasil Jagung Manis (Zea mays L. saccharata) pada Inceptisols Jatinangor - Septyani Sofatin; Betty Natalie Fitriatin; Yuliati Machfud (Soilrens, 2016)
Biofertilizer and N, P, K fertilizer combination is expected to decreased the application dosage of inorganic N, P, K fertilizer and increased the yield of maize. This experiment was conducted to describe the effect of N, P, K fertilizer and biofertilizer combination to the population total of soil microbes and yield of maize (Zea mays L. saccharata) on Inceptisols Jatinangor. This experiment was carried out Ciparanje Experimental Station, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor with altitude 820 meters from October 2015 to January 2016. This experiment was arranged in randomized block design which consisted of ten combinations and three replications. Ten combinations were: control; NPK standard dosage; biofertilizer standard dosage; ¼ of NPK + 1 of biofertilizer; ½ of NPK + 1 of biofertilizer; ¾ of NPK dosage + 1 of biofertilizer; 1 of NPK + 1 of biofertilizer; ¾ of NPK + ¼ of biofertilizer; ¾ of NPK + ½ of biofertilizer; and ¾ of NPK + ¾ of biofertilizer. The experiment showed that the combination of NPK and biofertilizer gave a significant effect to increased yield of maize. The standard dosage of biofertilizer reduced 50% of the NPK application and increased the yield of maize by 13,85% efficiently.Keywords: biofertilizer, NPK uptake, soil microbe, maize